The Impact Of Lifestyle And Product Attractiveness On Purchasing Decisions Aceh SMEs Coffee Products - Yusrawati; Syarifah Maihani; Saputra, Al Mahfud; Emi Safrina; Sri Murniyanti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This study aims to examine the purchasing decision factors of Small and Medium Enterprise (SMEs) coffee products in Bireun Regency, Aceh, Indonesia. Lifestyle and Product Attractiveness were tested as key predictors. Meanwhile, consumer attitudes as mediation. We approached as many as 500 coffee-loving youths to be sampled. However, 200 of them finally responded. Furthermore, the data was analyzed using the Structural Equation Modeling (AMOS-SEM) method. Based on the test results, lifestyle markedly has a positive and significant impact on attitudes, thus leading to purchasing decisions. Product attractiveness is known to have a significant impact on attitudes but cannot significantly impact purchasing decisions. Consumer attitudes are a link in influencing the lifestyle and attractiveness of local coffee products. Finally, it can be stated that the decision to purchase local coffee products has become the lifestyle of Acehnese youth today young people and the attractiveness of innovative products will help coffee SMEs players increase sales.